Patient satisfaction with services of private dental clinics in Riyadh city: A cross-sectional study - Hadi Rajeh Alfahadi; Nouf Sahal Alharbi; Fawaz Hamad Alkazman; Mohsen S. Alabbas (Saudi Journal of Oral Sciences)
Introduction: Patient satisfaction with health care describes the degree to which patients’ needs and expectations are met, and an acceptable level of service is provided. Additionally, it is also a measure of the quality of care that patients receive. Therefore, plays a major role in determining the relationship between the quality of healthcare services provided and patient confidence. It is important predictor of patient compliance, their ability to follow instructions, and their adherence to treatment, as well as for, determining their future use of health services. This is why patient satisfaction is increasingly considered as vital in assessing the general quality of care and thus in improving health services. Aims: This study set out to explore dental patients’ satisfaction with the service provided by private clinics in Riyadh in terms of accessibility, the availability and convenience of the facilities, cost, pain caused from dental procedures, the overall quality of treatment received, and the continuity of service. Materials and Methods: From January to February 2021, we conducted a cross-sectional study online survey of 420 patients to investigate their satisfaction the services provided by private dental clinics in Riyadh. Based on a previous questionnaire created by John, the online DSQ covered five key domains, namely, accessibility, cost, availability and convenience, pain, service quality, and additionally, overall level of satisfaction with the service. The resulting data were analyzed statistically using the SPSS-22 program and chi-square tests. Results and Discussion: The current study showed that, based on the demographics of the sample, among the five domains investigated, four were statistically significant as only the cost of dental procedures was not. Accessibility, availability, pain, and continuity were ranked highest among the younger participants and those with a lower educational level indicated greater pain from dental procedures. With regard to the quality of the dental service, again the youngest age group registered a higher level of satisfaction with the males taking the lead. Conclusion: The study showed that patient satisfaction with dental care is a valid measure of the quality of care and that having a service that meets the patients expected level of satisfaction should go a long way in helping to improve service delivery. Therefore, measuring the patients’ satisfaction with the service is an important factor in improving the service provided and so this should be done regularly.